Ekstraksi Konsentrat Protein Ikan Gabus (Channa Striata) Dengan Bahan Pengekstrak Aseton - Cindytia Prastari; Irnawati Sinaga; Listia Amanda (JURNAL PERIKANAN DAN KELAUTAN, 2023)
Snakehead has been reported to have high protein content and economic value. This study aims to determine: (1) nutritional content (proximate) fresh snakehead, (2) the results of snakehead fish protein concentrate, (3) nutritional content of snakehead fish protein concentrate, and (4) total amino acid content of fish protein concentrate snakehead. Research in five steps experiment: (1) preparation of fresh snakehead fish meat, (2) analysis of nutritional content (proximate) snakehead fish meat, (3) analysis of the results of snakehead fish protein concentrate, (4) analysis of nutrient content (proximate) concentrate snakehead fish protein, and (5) analysis of the total amino acid content of snakehead fish protein concentrate. The current study reported that the nutritional content (proximate) of fresh meat snakehead fish was 75.52% water (bb): 77.69% protein (bk); 4.18% fat (bk), 14.77% ash (bk), and 3.36% carbohydrate (bk). The average yield produced in the manufacture of snakehead fish protein concentrate was 69.87%. While the nutritional content (proximate) snakehead fish protein concentrate is 8.97% water, 66.07% protein, 0.89% fat; 11.53% ash, and 12.54% carbohydrates. The highest levels of amino acids in snakehead fish protein concentrate were lysine (6,12%) and tryptopan (5,89)